Molecular Docking of Abroma augusta Phytocompounds Against Estrogen Receptor Alpha (Er-Α) for the Treatment of Menstrual Disorders - Sanjana V. Rao (International Journal of Molecular Biotechnological Research, 2025)
Menstrual disorders, including dysmenorrhea (painful menstruation), amenorrhea (absence of menstruation), and irregular menstrual cycles, significantly impact women’s reproductive health and overall well-being. These conditions often arise from hormonal imbalances, inflammation, and uterine dysfunction, necessitating effective therapeutic interventions. Current treatments, such as hormonal therapies (oral contraceptives, progestin-only pills), NSAIDs, and surgical procedures (endometrial ablation, hysterectomy), provide relief but often target symptoms rather than addressing the underlying causes. Consequently, there is a growing interest in alternative plant-based therapies with gynecological benefits, with Abroma augusta emerging as a promising candidate. The objective of the study is to identify the potential phytocompounds of A. augusta and evaluate their therapeutic potential by analyzing their binding affinity with estrogen receptor alpha (ER-α) through molecular docking. By investigating the molecular interactions of these compounds, this research seeks to provide scientific validation for the traditional use of A. augusta and explore its potential as a natural therapeutic agent for menstrual disorders.
Keywords: Abroma augusta; Menstrual disorders; estrogen receptor alpha (ER-α); molecular docking